Modeling beam attenuation in solar tower plants using common DNI measurements. (May 2016) - Hanrieder, N.; Sengupta, M.; Xie, Y.; Wilbert, S.; Pitz-Paal, R.
Highlights: The transmittance model of Sengupta and Wagner (2011) is enhanced and validated. The model is enhanced by adapting altitude and water vapor content of validation site. Several aerosol height profiles and a correction for Linke turbidity are tested. The validation used 1 year of measured extinction data for Plataforma Solar de Almeráa. Abstract: Solar radiation reflected by concentrating mirrors is attenuated due to atmospheric extinction as it travels to the receiver of a solar tower plant. The lack of information on the magnitude of extinction increases the uncertainties in yield analysis and tower plant design. In-situ measurements of atmospheric extinction as well as measurement correction methods have been recently performed and developed (Hanrieder et al., 2012, 2015), but specific information is unavailable for individual plant projects. It is well known though that the extinction varies significantly with site and time. To overcome this absence of information a model to derive the attenuation loss between heliostat and receiver from common direct normal irradiance (DNI) measurements was developed by Sengupta and Wagner (2011) (SW2011 model). We present an updated version of that model and a comparison between the performance of the models using extinction measurements. In the new approach presented here, different precipitable water vapor (PWV) amounts are considered and the model is adjusted to the elevation of the investigated site. The strongest assumption in this approach is the assumption about the aerosol extinction height profile. Three different height profiles are tested for the Plataforma Solar de Almería (PSA) resulting in three different new transmittance models. The SW2011 as well as the three new models are evaluated with one year of corrected extinction data derived with the ABC (absorption and broadband correction) method of Hanrieder et al. (2015) and a Vaisala FS11 scatterometer at PSA. The new models show a mean difference to the reference data set of 0.01, 0.05 and 0.03 and a root mean square error (RMSE) of 0.052, 0.056 and 0.049 (compared to a mean bias of −0.08 and RMSE of 0.095 for the SW2011 model for transmittances through a 1 km slant range). These results indicate the importance of adequate assumptions for the aerosol height profile. Testing the developed TM with the LIVAS height profile (Amiridis et al., 2015) for PSA shows satisfying results and this motivates testing the approach for other sites. By applying an additional correction for the Linke turbidity (TL) derived as in Ineichen and Perez (2002) the mean bias can be further lowered. An uncertainty analysis shows that the absolute uncertainty coincide with the RMSE levels of the evaluation. Performing the additional TL correction promises an improvement of the overall performance of the model. The new models outperform the SW2011 model due to the PWV and elevation adjustments. The approach can be applied for different sites and incorporated in already existing ray-tracing or plant optimization tools. It is expected to be valuable for reducing uncertainty in power tower design and operations.